CODE MIXING IN HOT 20 COUNTDOWN OF PRAMBORS RADIO PROGRAM - DwiAstarini; Berlin Sibarani (State University of Medan, 2015)
This study deals with code mixing used by broadcasters in Prambors Radio,namely Hot 20 Countdown and SelamatPagi program. The objectives of the studywere (1) to find out the types of code mixing in Hot 20 Countdown andSelamatPagi, (2) to find out in what context code mixing used in Hot 20Countdown and SelamatPagi. The data of this study were the conversationbetween the broadcasters. This study applied descriptive qualitative method. Thefindings shows that there were 68 sentences of code mixing which were classifiedinto three types of code mixing, in Hot 20 Countdown there were 46 sentences, itconsists of 30 utterances (65,22%) insertion of code mixing, 15 utterances(32,61%) alternation of code mixing and 1 utterance (2,17) lexicalization of codemixing, while in SelamatPagi program there were 26 utterances, it consist 17utterances (77,27) of insertion code mixing, 4 utterances (4,55%) of alternationcode mixing, and 1 utterance (4,55%) of lexicalization code mixing.